Sleep disturbance and symptom burden in sarcoidosis. (November 2018) - Benn, Bryan S.; Lehman, Zoe; Kidd, Sharon A.; Miaskowski, Christine; Sunwoo, Bernie Y.; Ho, Melissa; Sun, Sara; Ramstein, Joris; Gelfand, Jeffrey M.; Koth, Laura L.
Abstract: Introduction: Sarcoidosis is a systemic inflammatory disease associated with myriad symptoms, including fatigue. It can affect physiological processes like sleep, leading to poor sleep quality and excessive daytime sleepiness. We hypothesized that sarcoidosis patients would report more severe sleep disturbance than healthy controls and that relationships would be found with sleep disturbance and the severity of other symptoms. Methods: We enrolled 84 sarcoidosis patients and 30 healthy controls and recorded demographic and clinical characteristics. Self-report measures were used to assess sleep disturbance, psychosocial symptoms, and quality of life at enrollment and longitudinally. Relationships between different self-report outcomes were analyzed using correlation statistics. Results: Using the General Sleep Disturbance Scale, 54% of sarcoidosis patients reported frequent and occasional sleep disturbance compared to only 17% of healthy controls (p < 0.0001). This significant increase in sleep disturbance found in sarcoidosis patients strongly correlated with multiple psychosocial symptoms, including fatigue, depression, and cognitive dysfunction, and negatively impacted quality of life (p < 0.01). Traditional measures of sarcoidosis disease severity or activity were not associated with sleep disturbance. Sleep disturbance scores remained stable at follow-up (mean time between first and last administration of questionnaire was 17.3 months) in 56 of the sarcoidosis patients. Conclusions: Sarcoidosis patients experienced significant sleep disturbance that correlated with higher levels of fatigue, depression, and cognitive dysfunction, and poorer quality of life. These associations were present regardless of disease severity or activity and result in decrements in quality of life and mental health. Highlights: Sleep-related disorders occur with increased frequency in sarcoidosis patients. We measured patient-reported outcomes of poor sleep in sarcoidosis. Sarcoidosis patients reported high levels of sleep disturbance. Higher sleep disturbance associated with other symptoms and reduced quality of life. Measures of disease severity were not correlated with severity of sleep disturbance.